Strategi Pengentasan Kemiskinan melalui Pemberdayaan Komunitas serta Revitalisasi Kelembagaan Ekonomi dan Sosial di Sulawesi Selatan - Syamsu Nujum (Jurnal Aplikasi Manajemen, 2012)
Poverty alleviation strategies through community empowerment as well as economic and social institution revitalitation in South Sulawesi. The purpose of this research were (1) to study the extent to which the roles of South Sulawesi government in empowering the marginal /poor community through various programs, (2) to study and explain the extent to which the benefits of poor community empowerment programs in efforts to alleviate poverty, (3) to study and explain poverty alleviation strategies which were suitable with local wisdom of local community in South Sulawesi. Approach type used in this research was qualitative with the use of primary and secondary data, but the main data were primary data which were obtained directly from research sources included individuals representing poor community, individuals refresenting government. Key informants were selected from this research subjects representing poor community, community figures and government. Data analysis technique used was descriptive technique by using phenomenology paradigm and Grand Theory. Research results show that strategies implemented by government did not yet touch the poor community as whole so that strategies which were suitable with local conditions were needed through involving local institutions as program supports in order to be effective. Poor community empowerment programs consisted of P2KP, KUT, PNPM-Mandiri, Raskin, and BLT. These programs gave benefits in alleviating rural and urban poverty but they did not run maximally because they only could serve a small part of the existing poor community. This research also build a model of empowerment in elleviating poverty through empowerment of micro, small and medium scale enterprises.Keywords: Poor Community Empowerment, Local Institutions